EVE’S DISSOCIATIVE IDENTITY DISORDER AS THE REFLECTION OF HER UNPLEASANT CHILDHOOD IN NUNALLY JOHNSON MOVIE, THE THREE FACES OF EVE - priyoto priyoto; lia aulia (Journal of English Language and Literature (JELL), 2019)
The objectives of this study are: (1) to explain the causes of Eve’s dissociative identity disorder. Eve has three identities in her body; Eve White, Eve Black and Jane; (2) to compare the personalities of each identity; and (3) to discuss more deeply the effect of Eve’s dissociative identity disorder to her psychological condition and her ways in facing dissociative identity disorder. This movie tells about dissociative identity disorder as the effect of unpleasant childhood. The personalities of each identity: Eve White, Eve Black and Jane are very different. They battle to be the master of its body. In analyzing this movie, the writer uses psychological approach because the problems of the movie relate to psychological issue like dissociative identity disorder. The method of research the writer used is qualitative. That means the method of this thesis deliver words rather than numbers as the data to be analyzed. The data in this thesis was collected by home-library. The writer reads books, journals, articles, and some offline books in collecting the data resources.